The Image of Music Promotor After Communication Crisis - Jade Nathania Sutanto; Inri Inggrit Indrayani; Astri Yogatama (Petra Christian University, 2025)
This study aims to understand the image of Mecimapro according to members of the X Day6 World Tour in Indonesia community following the communication crisis related to the Day6 concert payment system. The crisis sparked various public responses, reflected through the social media platform X (formerly Twitter), making it a significant medium in shaping public perception of the concert promoter’s image. This research employs a quantitative method using an online survey of 100 respondents aged 17 and above who are members of the X Day6 World Tour in Indonesia community. Image analysis is based on six dimensions of image according to Fill (1999): dynamic, cooperative, business, character, successful, and withdrawn. The results indicate that Mecimapro's image after the payment system communication crisis is categorized as negative. The crisis communication, which was perceived as slow, due to delayed official responses and lack of timely clarification, contributed to a negative perception among community members contributed to the formation of a negative perception among community members. This study highlights the importance of effective crisis communication management and the strategic use of social media in shaping and maintaining a company’s image, particularly in the entertainment industry.